Virtual promotion knowledge management technology - Orekhov, Sergey Valerievich; Malyhon, Hennadiy Vasilievich (Національний технічний університет "Харківський політехнічний інститут", 2020)
The article presents a new concept of “Management of knowledge about virtual promotion” on the Internet. Usually a real product or service is being divided into four components (product, price, promotion and place) in accordance with the theory of marketing. One of the components is a product promotion. But now this element is becoming a fully virtual tool. It is necessary to consider product promotion as an image or a copy of a real product in a virtual space that lives in parallel on the network. Therefore, the objective of the paper is the presentation of a new object of research based on the experience of more than thirty real projects performed in Ukraine, USA, Europe and Canada. We regard the promotion as a software product, which works according to principles of knowledge management and machine learning. It is proposed that virtual promotion is characterized by four views: customer or user, data, technology and marketing. Thus, the structure of virtual promotion business process was presented. It includes four steps: selection of hypertext sources, knowledge representation and extraction, semantic kernel building and quality criterion evaluation to stop the process. Based on the process structure the research tasks were identified. The central task is semantic kernel forming. Then the software architecture was developed. IT solution contains CRM system as accounting tool and Web site as an image of virtual promotion. CRM plays main role as a commander center. Here we form semantic kernel and then send it via marketing channels such as Web site, telegram or viber accounts. Another part of IT solution is Web service such as Bing API or Google API. They help us to build the kernel. Also the paper demonstrates the list of future tasks that should be solved and the example of real project of proposed approach.

У статті представлена нова технологія «управління знаннями про віртуальне просування» в мережі Інтернет. Звичайно реальний продукт або послуга характеризуються наступними компонентами: продукт, ціна, просування і місце, згідно з теорією маркетингу. Одним з компонентів є просування товару. Однак зараз цей елемент стає повністю віртуальним інструментом. Необхідно розглядати просування продукту як відображення або копію реального продукту у віртуальному просторі. Це відображення існує паралельно у мережі та безпосередньо впливає на реальний продукт чи послугу. Тому ціллю статті є презентація нового об’єкта дослідження, поява якого основана на досвіді виконання більш ніж тридцяти реальних проектів в Україні, США, Європі та Канаді. Ми працюємо відповідно до принципів управління знаннями і машинного навчання. Передбачається, що віртуальне просування характеризується чотирма репрезентаціями: клієнт або користувач, дані, технологія та маркетинг. Далі була представлена структура бізнес–процесу віртуального просування. Він включає чотири етапи: вибір джерел гіпертексту, подання та витяг знань, побудова семантичного ядра і оцінка критерію якості для зупинки процесу. На основі структури процесу були визначені задачі дослідження. Центральна задача – формування семантичного ядра. Потім була розроблена архітектура програмного забезпечення. ІТ рішення містить CRM систему в якості інструменту обліку та Веб сайт як образ віртуального просування. CRM грає роль командного центру. Тут формується семантичне ядро і потім відправляється через маркетингові канали, такі як Веб сайт, Телеграм канали або профілі в Вайбері. Інша частина ІТ рішення – це Веб сервіс, такий як Bing API або Google API. Вони допомагають нам побудувати ядро. Також в статті наведено список майбутніх завдань, які необхідно вирішити, і приклад реальних проектів в рамках запропонованого підходу.
Технологія управління знаннями про віртуальне просування
Keywords: Product promotion; CRM; SEO; просування продукту; CRM; SEO